Mendeteksi Indikasi Manipulasi Laporan Keuangan Menggunakan Model Altman dan Beneish - Maulida Salmi Utie; Siti Nurwahyuningsih Harahap (Politeknik Ganesha Medan, 2025)
The study focuses on the relationship between financial distress and indications of financial statement manipulation by PT AISA. Until 2017, PT AISA was in good financial condition as indicated by the published financial statements and the unqualified opinion obtained from the external auditor. However, in 2018, PT AISA experienced a default which resulted in the suspension of shares from the IDX and default status on the bond rating from PEFINDO. In this case, an investment was made by EY which showed indications of financial statement manipulation by PT AISA. The AISA case was made the subject of research using quantitative methods. The data used came from PT AISA's financial statements since the IPO in 2003 to 2017. The Z-score model (Altman, 1968) and M-score (Beneish, 1999) were used to analyze the financial statement data. The results of the analysis show that the use of both models simultaneously can identify the relationship between financial statement manipulation and financial performance.